(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Since ancient times, cities have been the complex locus of human coexistence. They are political societies, allowing citizens to participate more actively and democratically in coexistence with their fellow human beings. In Brazil, the City Statute (Law n° 10.257/2001) guarantees the right to sustainable cities, understood as the right to urban land, housing, environmental sanitation, urban infrastructure, transportation and public services, work, and leisure, for present and future generations. Inspired by the UN Agenda 2030 and ILO standards in favor of decent work, the promotion of decent green jobs is paramount, as municipal public policies capable of collaborating in the construction of sustainable cities, with the association between decent work and environmental, social, economic, and other sustainability. Citizens have the subjective public right to inhabit sustainable cities in accordance with the 2030 Agenda, which, although global, ties its implementation to the local level in municipalities. Thus, the study aimed to raise awareness among citizens and the municipal government about the right to sustainable cities and its imperative implementation for present and future generations